Local measurement of hot-electron phase-coherence at metal surfaces - Schneider, M. Alexander; Wahl, P; Vitali, L; Diekhöner, L; Vogelgesang, Ralf; Kern, Klaus (Applied Physics A: Materials Science and Processing, 2007)
We use scanning tunneling microscopy and spectroscopy to study the energy dependence of hot-electron scattering processes on metal surfaces via the determination of the energy-dependent phase-coherence length. From this an electron lifetime can be determined, which in the case of electrons in the surface state of Ag(111) and in the case of the n=1 image-potential state on Cu(100) shows good agreement with theoretical modeling and other experimental data. The method is based on the quantitative analysis of electron interference patterns. A theoretical analysis shows that the phase-coherence length can be determined in confining nanostructures of a characteristic length scale smaller than the phase-coherence length.<br
Keywords: Scanning Tunneling Microscopy; Coherence Length; Noise Band; Scanning Tunneling Spectroscopy; Standing Wave Pattern